Effectiveness of Balloon Angioplasty Compared with Coronary Stenting in Narrow Coronary Arteries (Medical Forum Monthly, 2023)
Objective: The study aimed to assess the effectiveness of balloon angioplasty compared with coronary stenting in narrow coronary arteries.Study Design: A comparative studyPlace and Duration of Study: This study was conducted at the department of cardiology, Lady Reading Hospital Peshawar. The study duration was one year from June 2022 to June 2023.Methods: This comparative study was carried out at the department of cardiology, Lady Reading Hospital Peshawar. The study duration was one year from June 2022 to June 2023. A total of 100 patients with lesions in narrow coronary arteries were enrolled. Participants were randomly allocated to get stent placement or traditional balloon angioplasty. Each participant signed a written statement of informed permission. During a year, the rates of clinical events were assessed. SPSS version 25 was used for descriptive statistics.Results: Total 100 patients were enrolled in this study. Male patients were 59(59%) and female patients were 41 (41%). Each group consists of 50 patients with comparable baseline demographics and angiography findings. Major adverse cardiac events and the rate of success of angiography were equivalent, according to treatment analysis: 5.4% and 95.6% in the case of coronary stenting and 5.6% and 93.5% in the case of balloon angioplasty. 3.8% of patients had significant closure changes throughout the course of 30 days. At six months, stenting substantially increased the lumen by1.52 mm and balloon angioplasty by 1.32 mm. (p=0.002) and the post-procedural lumen diameter was increased 2.31mm by stent and 1.82 mm by balloon angioplasty (p=0.002). The restenosis incidence after coronary stenting and balloon angioplasty was found to be 35% and 55%, respectively. The survival rates (event-free) after coronary stenting and angioplasty were respectively 75% and 65% (p=0.034).Conclusion: Our study concludes that lesions in narrow coronary arteries may respond well to optimum balloon angioplasty with subsequent stenting. The restenosis rates were reported to be 35% and 55% in coronary stenting and balloon angioplasty respectively.